Standardization of a galactogogue herbal mixture based on its total phenol and flavonol contents and antioxidant activity - N. Kahkeshani; A. Hadjiakhoondi; N. Maafi; M. Khanavi (Iranian Society of Pharmacognosy, 2015)
Background and objectives: Dairy companies always try to increase the quantity and quality of milk production. According to the positive impact of different plants on milk production of cattle, this study was carried out to standardize a galactogogue herbal mixture based on its total phenol and flavonol contents and antioxidant activity.  Methods: A mixture of Galega officinalis L. and Nigella sativa L. powders (4:1 w/w), which had shown milk stimulating activity on Holstein cows in a previous study, was extracted with hydro alcoholic solvent (80% aq. methanol) and its 1,1-diphenyl-2-picryl-hydrazyl (DPPH) radical scavenging activity and total phenol and total flavonol contents were measured according to standard methods. Results: The inhibition concentration 50% (IC50 ) value of radical scavenging activity in DPPH test and the total phenol and total flavonol contents were found to be 154.29 µg/mL, 77.720±0.104 µg of gallic acid equivalent (GAE) and 0.231±0.018 µg of quercetin equivalent (QE) per mg of dry extract, respectively. Conclusion: This herbal extract can be standardized based on its antioxidant activity or total phenol and total flavonol contents and the standardized extract can be formulated as a veterinary galactogogue supplement.